Neuromarketing as a factor influencing consumers - Potapov, F. V.; Pererva, P. G. (Національний технічний університет "Харківський політехнічний інститут", 2023)
It has been proven that in the use of special technologies that allow you to literally "see" the processes of the brain, there is a fundamental difference between neuromarketing and classical marketing, when focus groups of respondents are formed and questions are asked to their participants.
Нейромаркетинг як фактор впливу на споживачів
Keywords: market; neuromarketing; advertising; factors; consumers; supply; demand